Total Antioxidant Capacity of Serum Determined Using the Potassium Permanganate Agar Method Based on Serum Diffusion in Agar - Ying Zhou; Meijuan Zhang; Hui Liu (Bioinorganic Chemistry and Applications)
Objectives. To develop a new method for determining total antioxidants in serum and to evaluate the total antioxidant capacity of organisms. Design and Methods. Sodium hyposulfite (Na2S2O3) and serum were used to evaluate the linearity and precision of the potassium permanganate agar method. The area of serum diffusion in samples from 30 intensive care unit (ICU) patients compared with 44 healthy subjects was determined by the potassium permanganate agar method. Results. The linearity (R2 in the linear experiment of Na2S2O3 was 0.994; R2 in the linear experiment of serum was 0.987) and precision (coefficient of variation of area of high level serum diffusion within-run, between-run, and between-day and coefficient of variation of area of low serum diffusion within-run, between-run, and between-day were all less than 10%) were acceptable using the potassium permanganate agar method. Total antioxidants of serum between the ICU group and the healthy group were different (p=0.002, two tailed). Conclusions. Total antioxidants in serum can be determined by the potassium permanganate agar method. The total antioxidant capacity of an organism can be evaluated by the amount of total antioxidants in serum.